Non-specific acute abdominal pain - Guicheff, Vladimir; Ferreira, Ciro (Cirugía del Uruguay, 1984)
By non-specific abdominal pain it is designated pain in respect of which it is lmpossible to determine to what known classification it belongs. The high frequency of same, ranging from 24 and 49% in statistical data consulted, merits to be taken into account when deciding upon procedures. Decisions in that respect should result from a complete clinical examination of the patient and a discerning ponderation of auxiliary methods available, to permit a decrease in the number of unnecesary interventions. Certain axioms of interventionism concerning the acute abdomen should be restated in view of the high rate of morbimortality in blank laparotomy.